Pharmacokinetic Characteristics of Long-Acting Injectable Antipsychotics for Schizophrenia: An Overview - Correll, Christoph U.; Kim, Edward; Sliwa, Jennifer Kern; Hamm, Wayne; Gopal, Srihari; Mathews, Maju; Venkatasubramanian, Raja; Saklad, Stephen R. (CNS drugs, 2021)
The availability of long-acting injectable (LAI) antipsychotics for the treatment of schizophrenia provides clinicians with options that deliver continuous drug exposure and may improve adherence compared with daily oral antipsychotics. However, all LAI antipsychotics have unique formulations and pharmacokinetic characteristics that have implications for medication selection, administration interval, and injection site. This review outlines key differences in drug formulations and pharmacokinetics among LAI antipsychotics. A systematic search of the PubMed database was conducted to identify physical and formulation properties and pharmacokinetic data of commercially available LAI antipsychotics, including flupentixol decanoate, fluphenazine decanoate, haloperidol decanoate, zuclopenthixol decanoate, aripiprazole monohydrate, aripiprazole lauroxil, olanzapine pamoate, paliperidone palmitate, risperidone microspheres, and risperidone polymeric microspheres. Additional information was obtained from package inserts and product monographs. Relevant data on drug properties, administration details, pharmacokinetic parameters, and oral dose equivalencies of LAI antipsychotics are summarized. Based on our analysis, formulation characteristics (e.g., vehicle medium) and administration characteristics (e.g., injection site) can affect rate of absorption and adverse effects and may factor into whether oral supplementation or an additional injection is needed. Dose adjustments may be necessary based on potential drug–drug interactions, and approximate dose equivalence with oral formulations can help inform titration when switching from oral to LAI formulations. Clinicians administering LAI antipsychotics should consider these formulation and pharmacokinetic factors to maximize clinical impact and to adjust to an individual patient’s needs and treatment goals.